Standard survival model with two and three parameter weibull distributions :ba comparative study - 494552 Nur Intan Syafinaz Ahmad; Zarina Mohd Khalid, supervisor; Fakulti Sains (2009)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2009